Analisis Nilai-Nilai Pendidikan dalam Novel “Pada Senja yang Membawamu Pergi” Karya Boy Candra- Yanida Buulolo: Novel "Pada senja yang Membawamu Pergi" - Yanida Bu'ulolo (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is based on the researcher's observations on literary works, one of which is the novel. This study aims to describe, and explain the educational values ​​contained in the novel "At the Senja that Takes You Go" by Boy Candra. These educational values ​​include the value of character education, intelligence, social, citizenship, aesthetics, physical and family welfare. The research method used is descriptive research method and the type of qualitative research, using a pragmatic approach. Based on the results of the study, it can be concluded that in the novel "At Twilight that Takes You away" by Boy Candra, there are values ​​of character education, intelligence, social, citizenship, aesthetics, physical and family welfare which can indirectly provide a learning, upbringing, role model. and good qualities that can affect the lives and character of students in schools so that they can have good morals